Low re-inhalation of the exhaled flow during normal nasal breathing in a pediatric airway replica. (15th February 2016) - Wei, Jianjian; Tang, Julian W.; Borojeni, Azadeh A.T.; Yin, Shi; Martin, Andrew; Finlay, Warren H.; Li, Yuguo
Abstract: To estimate the fraction of the exhaled airflow that is re-inhaled during normal nasal breathing, experiments were carried out in a water tank with an anatomically accurate respiratory tract model of a 4-year-old child. The velocity of respiratory flow was scaled using similarity laws between air and water. Breath simulation was performed via a computer-controlled piston-cylinder system. Food-dye visualization allows a qualitative analysis of the re-inhaled fraction of this exhaled flow. For the quantitative analysis, neutrally buoyant particles were added to the water medium, and illuminated by the laser which illuminates the whole breathing region of the respiratory model, such that the trajectory and quantity of the re-inhaled particles can be recorded and counted. The experimental results in the pediatric airway replica show that a negligible fraction (<0.06%) of the exhaled airflow is re-inhaled during normal nasal breathing in the absence of the rising thermal plume. The artificial plume generated by a heated aluminium brick at the tank bottom increases the re-inhalation ratio by 4 times under the investigated case (albeit still at a very low value of 0.15%). Our results thus reveal that during normal nasal breathing in the present pediatric subject, the vast majority of human exhaled airflow escapes from the inhalation zone and is not re-inhaled. Highlights: The transient breathing cycle was experimentally investigated. A 3-D replica of human respiratory tract was used. It was the first attempt to use the laser & particle quantitative method. The dynamic interaction between the exhaled flow and the plume was studied.